On the role of challenging math problems in the discrete mathematics courses - Mihova, Marija; Jovanov, Mile; Stankov, Emil (IEEE, 2015)
Mathematical talent must be identified through a range of measures that go beyond usual activities and traditional standardized tests. One possibility that we use at our institution is additional assessment through challenging math problems. In this paper we present the results of our experience in the organization of Discrete Mathematics faculty courses, with emphasis on the role of challenging math problems. The results were gathered in the period of 3 academic years, in courses with more than 500 enrolled students each. These results justify and enforce the use of such problems.